Prevention and Countermeasures of Wild Levies on Behalf of Indigenous Villages - Ni Putu Yunika Sulistyawati; Sang Ayu Made Ary Kusumawardhani (Dwijendra University, 2021)
The purpose of this research is to find out the Prevention and Countermeasure of Wild levies on behalf of indigenous village. The type of research used in this research is empirical research. Empirical research is research that examines and analyzes the legal workers in society (law in action) the main data used is data sourced from the Prevention and Countermeasure of wild levies on behalf of indigenous village. The results indicate that the prevention and countermeasures of Wild levies on behalf of Indigenous Villages. The goals of community welfare and community protection, prevention and countermeasures of crime must be carried out with integral of the means of reasoning penal and non-penal. Viewed from the political point of the most strategic policy law through preventive, preventive and countermeasures of crime by means of reasoning and non-precision whose functionalization or operationalization through several stages, namely, the legislative policy stage, the judicial policy stage and the executive policy stage. Repressive efforts are a last resort in overcoming illegal levies efforts made to suppress the magnitude of the number of Hungarian criminal acts in order to have a deterrent effect and fear for perpetrators or communities who are later in wanting to commit criminal offenses will undo the intentions of the repressive legal remedies.